Comparison of Intrinsic Elements of Indonesian and German Children's Literature to Enrich Character Education for Indonesian Children - Meutia Hawa, Andina; Prades Pratiwi, Dyani; Saniro, Roma Kyo Kae; Arbain, Armini (ELT-Lectura, 2024)
Children's literature has many benefits, including being a medium of entertainment and a medium for character education for children. Children's literature contains various noble values that readers can internalize daily. This research uses two objects of children's literature: the Indonesian children's literature book Dru dan Negeri Lima Kerajaan by Clara Ng and Renata Owen and the German novel Apfelkuchen und Baklava by Kathrin Rohmann. This research aims to compare two intrinsic elements from the two novels as material for character education for students in Indonesia. The intrinsic elements in both novels are characters, setting, theme, and message. The research results show that the intrinsic elements of both novels have symbolic meanings that contain noble values such as patience, courage, kindness, sincerity, acceptance, and openness. Therefore, it can be concluded that the two novels can be used as material for enriching student and Indonesian character education and cultivating global character.